(untitled) (Biological Sciences - PJSIR, 2002)
Meat samples of 15 different edible animal species from fish, birds and mammals were collected for laboratory studies from Multan. It was observed that % water was found to be 75.41 ± 2.75, 72.52 ± 1.5, 74.34 ± 2.37; % fat 2.61± 0.44, 3.01 ± 0.47, 2 .76 ± 0.67; % protein 20 . 93 ± 5.97, 23.54 ± 1 .31, 22.03 ± 1.77; % ash 2.41 ± 2.74, 0.93 ± 0.26, 0.89 ± 0.16 i n catfish, birds and mammals respectively when expressed on wet weight basis. ANOVA revealed that among fish , birds and mammals the % water, % fat and % protein content were found to be similar (P>0.05). Percent ash was significantly higher in catfish than bi rds and mammals (P<0.001). Economically , the significantl y cheapest source of protein was found to be catfish parallel to cattle but fish has nutritional superiority.